You are not what you eat during physiological stress: Isotopic evaluation of human hair - D'Ortenzio, Lori; Brickley, Megan; Schwarcz, Henry; Prowse, Tracy (American journal of physical anthropology, 2015)
ABSTRACT Variation in δ13C and δ15N values can be assessed to understand not only diet, but also the influence of physiological factors on an individual. The metabolic balance of an individual can impact isotopic signals in tissues that are forming during the periods of metabolic stress. Fluctuating δ15N values are associated with physiological stressors that alter an individual's metabolism such as infection, injury, or pregnancy. This study examines variation in δ13C and δ15N values along sequentially segmented hair in both modern and archaeological individuals. Subjects with an observable skeletal pathology, known chronic illness, or evidence of pregnancy were compared with controls exhibiting no evidence of physiological stress. The results on hair samples from individuals from 19th century Belleville, Ontario, four modern cadavers (two with cancer and two sudden deaths), and two living pregnant women indicate that δ15N values are approximately 1‰ higher in individuals with a pathological condition (e.g., infection, fracture, or cancer) and are 1‰ lower during pregnancy, whereas δ13C values show less variability. Higher nitrogen values may represent the recycling of nitrogen derived from the breakdown of existing proteins in the body (catabolism), whereas lower δ15N values are related to increased utilization of dietary and urea nitrogen for tissue synthesis during pregnancy. These findings suggest that short‐term fluctuations of δ15N values may be the result of changes in an individual's metabolic balance, and that metabolic imbalance poses a confounding factor to ancient dietary studies when using rapidly growing tissues such as hair. Am J Phys Anthropol 157:374–388, 2015. © 2015 Wiley Periodicals, Inc.